2019
DOI: 10.1016/j.drugalcdep.2019.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual cycle phase modulates responses to smoking cues in the putamen: Preliminary evidence for a novel target

Abstract: Background: The preclinical literature identifies the ventral striatum (VS) as a key player in drug-conditioned responses, guiding hypotheses examining neural substrates involved in human drug cue reactivity, including the study of sex differences. Men show a replicable response that includes the VS, while women's responses have been weaker and variable. New evidence suggests that the hormonal milieu modulates women's responses to drug cues in the dorsal striatum (DS), specifically, in the putamen. Here we tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Moreover, women showed greater activation in the right DS (putamen and caudate) when choosing sooner rewards in the late FP than when do so in the mid-LP (i.e., SFP > SLP), indicating that the right DS is more responsive to immediate rewards during the late FP than during the mid-LP. These results are consistent with the prior findings showing that a heightened drug cue-responsivity in women is associated with enhanced activity in the DS, especially in the putamen ( Cummings et al, 2014 ; Franklin et al, 2019 ). Indeed, behavioral impulsivity has been linked to dopamine levels in the putamen.…”
Section: Task Fmri Studysupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, women showed greater activation in the right DS (putamen and caudate) when choosing sooner rewards in the late FP than when do so in the mid-LP (i.e., SFP > SLP), indicating that the right DS is more responsive to immediate rewards during the late FP than during the mid-LP. These results are consistent with the prior findings showing that a heightened drug cue-responsivity in women is associated with enhanced activity in the DS, especially in the putamen ( Cummings et al, 2014 ; Franklin et al, 2019 ). Indeed, behavioral impulsivity has been linked to dopamine levels in the putamen.…”
Section: Task Fmri Studysupporting
confidence: 93%
“…Region of interest analyses were conducted to further refine our hypothesis. ROIs were selected based on our hypotheses and previous studies ( Cummings et al, 2014 ; Franklin et al, 2019 ). Based on prior relevant work ( Pine et al, 2010 ), the following Montreal Neurological Institute (MNI) coordinates for bilateral ROIs were defined: putamen, MNI coordinates 30 −3 −12 and −24 12 −9; caudate, MNI coordinates 21 24 −3 and −9 12 9; and dlPFC, MNI coordinates 42 18 27 and −45 33 18.…”
Section: Task Fmri Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of sex/gender, multiple studies have demonstrated sex- /gender-related differences in FDCR, particularly in participants who smoke cigarettes (Francis J. McClernon, Kozink, & Rose, 2008; Wetherill et al, 2013), individuals with cocaine dependence (Joseph et al, 2019; Potenza et al, 2012), and those with gambling (Kober et al, 2016) and gaming (Dong, Wang, Du, & Potenza, 2018; Dong, Wang, Wang, Du, & Potenza, 2019; Dong, Zheng, et al, 2018) disorders, which may depend, in part, on menstrual cycle phase in women (T. R. Franklin, Jagannathan, Ketcherside, Spilka, & Wetherill, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Because older adults have been routinely excluded from MRI studies that do not focus on aging, and taking into account shared neurodegenerative impacts of addiction and biological aging (Cheng et al, 2013), there is relatively little known about FDCR in older adults (e.g., > 65-years). In terms of sex/gender, multiple studies have demonstrated sex-/gender-related differences in FDCR, particularly in participants who smoke cigarettes (Francis J. McClernon, Kozink, & Rose, 2008;Wetherill et al, 2013), individuals with cocaine dependence (Joseph et al, 2019;Potenza et al, 2012), and those with gambling (Kober et al, 2016) and gaming Dong, Wang, Wang, Du, & Potenza, 2019;Dong, Zheng, et al, 2018) disorders, which may depend, in part, on menstrual cycle phase in women (T. R. Franklin, Jagannathan, Ketcherside, Spilka, & Wetherill, 2019).…”
Section: Participant Characteristicsmentioning
confidence: 99%